Sintonia de controladores PID a partir do Método do Relé - Torres, Juan Carlos Villadiego (2004)
In this work, two tuning strategies for PID controllers, based on system identification using relay test, were presented. In the first of them, named Second Order System Tuning - MASO, two points of the FRF are known, static and natural frequency points. In the second one, named Variety System Tuning - MASV, system features were collected after analysing its FRF. In this method, closed loop bandwidth and closed loop transfer function were selected automatically. These two approaches were numerically and experimentally tested for three and thirteen systems respectively using two lab benches. For testing the first methodology, a Texas Instruments eZdsp card, based on a TMS320LF2407A DSP processor, was employed to identify the system and to tune the PID controller. In this workbench, the system was a one degree-of-freedom low damped oscillating table. To develop the MASV method, a cantilevered beam was tested using piezoelectric - PZT - actuators. Identification and tuning algorithms were programmed on Simulink®, associated in dSPACE® and gathered using a signal acquisition card. The first approach, made by MASO, only uses second order reference systems, showed like a particular case from MASV strategy, which take into account a diversity of reference systems. Main conclusions showed that numerical and experimental designed controllers for one and multiple degree-of-freedom low damped systems, were satisfactories, because they achieved better controlled behaviors than the required conditions. Also, digital signal processor technology was considered as a powerful tool on digital control system applications